Construction and characterization of an infectious cDNA clone of coxsackievirus A 10 - Qiliang Liu (Virology Journal, 2019)
Abstract Background Coxsackievirus A10 (CA10) constitutes one of the four major pathogens causing hand, foot and mouth disease in infants. Infectious clones are of great importance for studying viral gene functions and pathogenic mechanism. However, there is no report on the construction of CA10 infectious clones. Methods The whole genome of CA10 derived from a clinical isolate was amplified into two fragments and ligated into a linearized plasmid vector in one step by In-Fusion Cloning. The obtained CA10 cDNA clones and plasmids encoding T7 RNA polymerase were co-transfected into 293 T cells to rescue CA10 virus. The rescued virus was identified by SDS-PAGE, Western blotting and transmission electron microscopic. One-day-old ICR mice were intracerebrally inoculated with the CA10 virus and clinical symptoms were observed. Multiple tissues of moribund mice were harvested for analysis of pathogenic changes and viral distribution by using H&E staining, real-time PCR and immunohistochemical staining. Results CA10 viruses were rescued from the constructed cDNA clone and reached a maximum titer of 108.125TCID50/mL after one generation in RD cells. The virus exhibited similar physical and chemical properties to those of the parental virus. It also showed high virulence and the ability to induce death of neonatal ICR mice. Severe necrotizing myositis, intestinal villus interstitial edema and severe alveolar shrinkage were observed in infected mice. The viral antigen and the maximum amount of viral RNA were detected in limb skeletal muscles, which suggested that the limb skeletal muscles were the most likely site of viral replication. Conclusion Infectious clones of CA10 were successfully constructed for the first time, which will facilitate the establishment of standardized neonatal mouse models infected with CA10 for the evaluation of vaccines and antiviral drugs, as well as preservation and sharing of model strains.